Molecular identification and antibacterial activity of endophytic bacteria from Bambusa vulgaris leaves as antibacterial potential against phatogenic microoganism - Jekmal Malau; Vriezka Mierza; Munir Alinu Mulki; Lestari Mahardika Urbaningrum; Vina Luthfiana Hasna; Priscinya Christiana Debora (Universitas Nahdlatul Ulama Surabaya, 2025)
The increasing prevalence of antibiotic-resistant bacteria poses a critical global health concern, necessitating the exploration of novel antibacterial solutions. Endophytic bacteria, which colonize plant tissues without causing harm, have gained attention as potential sources of bioactive metabolites. This study aimed to isolate and characterize endophytic bacteria from Bambusa vulgaris leaves and evaluate their antibacterial potential against pathogenic microorganisms. Leaf samples were collected from Bekasi, West Java, and subjected to a surface sterilization process prior to bacterial isolation. A total of 12 bacterial strains were successfully obtained and screened for antibacterial activity against Bacillus subtilis, Propionibacterium acnes, Pseudomonas aeruginosa, and Staphylococcus epidermidis using the agar well diffusion assay. Three isolates exhibited notable inhibitory activity, with P8 demonstrating the strongest antibacterial effects against B. subtilis, P. acnes, and S. epidermidis. The two most potent isolates, P8 and K3, were characterized via 16S rRNA gene sequencing. Genomic DNA extraction was performed, followed by Polymerase Chain Reaction (PCR) amplification using the universal primers 27F (5′-AGAGTTTGATYMTGGCTCAG-3′) and 1492R (5′-GGTTACCTTGTTACGACTT-3′). Sequencing and The Basic Local Alignment Search Tool (BLAST) analysis confirmed that isolate P8 exhibited 100% similarity to B. subtilis strain LZH-H1, whereas isolate K3 shared 99.85% similarity with Pantoea stewartii subsp. indologenes strain SR2-12. These findings suggest that endophytic bacteria from B. vulgaris endohytic bacteria hold promise as potential sources of antibacterial compounds. Further research is necessary to purify and characterize these bioactive metabolites for potential pharmaceutical applications.